Redesigning Electoral Democracy in the Regional Representative Council (DPRD) Following Constitutional Court Decision No. 135/PUU-XXII/2024: English - Muni, Abd. (Jurnal Penegakan Hukum dan Keadilan, 2026)
This article aims to explore the redesign of Indonesian electoral democracy following Constitutional Court Decision No. 135/PUU-XXII/2024, which separates national and regional elections. This separation has significant implications for the institutional architecture of democracy, particularly regarding the term of office of regional legislatures. The decision has the potential to trigger disharmony with the provisions of Article 22E of the 1945 Constitution, Paragraphs 1 and 2, and the MD3 Law, which stipulates a five-year term for the Regional People's Representative Council (DPRD). This disharmony could lead to a vacuum in regional legislative power, as the 2024 national election ends in 2029, while regional elections will not be held until 2031. The focus of this research is the implications of Decision No. 135/PUU-XXII/2024 on electoral democracy, the normative legal review of DPRD electoral democracy, and the strategy for redesigning electoral democracy following Decision No. 135/PUU-XXII/2024. This research employs a normative juridical method with a legislative approach and is based on Arend Lijphart's institutional design theory, which emphasizes the importance of institutional stability and consistency in a democracy. The results suggest three points. First, there is a need to revise or harmonize regulations related to legislative schedules and terms. Second, an anticipatory institutional transition design, such as term extensions or the appointment of temporary officials, is needed. Third, coordination between state institutions must be strengthened to ensure effective implementation of Constitutional Court decisions without disrupting government stability.